Abstracts of the 2nd International Electronic Conference on Clinical Medicine (ECCM 2024) - Emmanuel Andrès; Kent Doi (Medical Sciences Forum, 2024)
The 2nd International Electronic Conference on Clinical Medicine: Chronic Diseases—Current State and Future Trends (ECCM 2024) was organized by MDPI and MDPI Journal of Clinical Medicine and took place online from 13 to 15 November 2024. This conference report is an abstract collection from different sessions of ECCM 2024.